2018
DOI: 10.1002/bies.201800017
|View full text |Cite
|
Sign up to set email alerts
|

Cells in the Non‐Uniform Magnetic World: How Cells Respond to High‐Gradient Magnetic Fields

Abstract: Imagine cells that live in a high-gradient magnetic field (HGMF). Through what mechanisms do the cells sense a non-uniform magnetic field and how such a field changes the cell fate? We show that magnetic forces generated by HGMFs can be comparable to intracellular forces and therefore may be capable of altering the functionality of an individual cell and tissues in unprecedented ways. We identify the cellular effectors of such fields and propose novel routes in cell biology predicting new biological effects su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 87 publications
0
30
0
Order By: Relevance
“…We observed that the DNA replication was decreased by about 5%‐15% by upward direction SMF in four different cell lines, while downward direction SMF did not generate such effect (Figure ). It should be noted that different types of cells exhibit different responses to SMF because this response depends on many factors, such as cell type, age, differentiation state, cell rigidity, cell polarity, and other external factors influencing the cell machinery …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We observed that the DNA replication was decreased by about 5%‐15% by upward direction SMF in four different cell lines, while downward direction SMF did not generate such effect (Figure ). It should be noted that different types of cells exhibit different responses to SMF because this response depends on many factors, such as cell type, age, differentiation state, cell rigidity, cell polarity, and other external factors influencing the cell machinery …”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that different types of cells exhibit different responses to SMF because this response depends on many factors, such as cell type, age, differentiation state, cell rigidity, cell polarity, and other external factors influencing the cell machinery. 39 Since Topoisomerases could alter the supercoiling of double-stranded DNA, we chose topotecan, a topoisomerase I inhibitor 40,41 that can interfere with supercoil relaxation, in combination with SMFs. Two colon cancer cell lines HCT116 and LoVo were plated first day and treated with corresponding concentrations of topotecan or DMSO as control for another 2 days before they were harvested for analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acting with these possible forces, an organism can experience unique effects under an SMF, namely HGMF, which could be a varying gradient MF created by using a Maxwell coil or a constant gradient MF that coexists with the homogeneous SMF at the off-center positions as shown in Figure 1B. An HGMF normally refers to a gradient higher than 10 3 Tm -1 because, in such an MF, the cells would experience a magnetic gradient force with the same volume density as that of gravity (40). Apart from the macroscopic HGMF, magnetic NPs could also induce a local HGMF around single cells as reported by Tseng et al Localized, NP-mediated magnetic forces were applied to HeLa cells through an MF with a gradient from 2.5×10 3 Tm −1 to 7×10 4 Tm −1 (41).…”
Section: Mechanical Deformation Of Immune Cells With Mfsmentioning
confidence: 99%
“…In fact, the electrostatic contribution of bending energy from charged cell membranes is large, and the cell membrane rigidity is proportional to the square of the membrane voltage [Zablotskii et al, 2016b]. Therefore, by changing the membrane voltage, one can also control cell rigidity, which might be important for cancer cells that have paradoxically small membrane potentials [Levin, 2009[Levin, , 2014[Levin, , 2020, allowing them to be very plastic with high invasive abilities [Zablotskii et al, 2018].…”
Section: Membrane Potentialmentioning
confidence: 99%